Theoretical aspect of the category "innovation potential" of a construction company - Matsapura, O.V.; Dzyubko, T.V.; Vlasenko, N.V.; Kalashnik , K.V. (Ways to Improve Construction Efficiency, 2020)
The article presents the results of analytical research of scientific literature of domestic and foreign researchers, which allowed to determine the essence of the definition of "innovative potential" of a construction company. For this purpose, the article considered such scientific categories as innovation potential and innovation potential of the enterprise. Analysis of the works of famous scientists shows that the innovation potential today is positioned as one of the basic concepts of innovation theory. However, on the question of the essence of the category "innovation potential", as well as the factors influencing its formation, there are often diametrically opposed views. Such variability involves the explication of innovation potential by describing the properties of the internal state of the subject of innovation, as a set of tangible and intangible subsystem of innovation potential. After working on these concepts, we came to the conclusion that the innovative potential of a construction company should be considered as a combination of three components: innovative construction methods, construction from innovative materials and innovative human resources. That is why we propose to consider the innovative potential of the construction company as a total wealth of internal potentials of the enterprise, which allows to develop and successfully implement innovations in all areas of the construction company. Innovative activity is the readiness and ability of an innovative enterprise to carry out for the first time and to implement innovations in further activities. The article uses a historical approach and a comparative analysis of theoretical approaches to the concept of "innovation potential", resulting in. found that the essence of this definition includes not only economic but also resource component. We propose to consider the innovative potential of the construction company as a total wealth of internal potential of the company, which allows to develop and successfully implement innovations in all areas of activity.